Three essays in applied development economics - (:unkn) unknown (My University, 2019)
This thesis is a collection of three independent research project in applied development economics. The first chapter studies the behavior of local Chinese Communist Party secretaries between 1996 and 2014, and the economic performance of their prefectures. It shows that the Chinese political system incentivizes local bureaucrats to generate high growth, and that this translates into higher real estate investment and higher expropriation rates of rural land. The second chapter looks at the consequences of the 2008 global financial crisis on the internal migration patterns in China. It shows that the apparent stability of aggregate migration rates hides substantial heterogeneity across individuals of different characteristics. The third chapter evaluates the impact of the non-contributory Old Age Pension scheme in South Africa. It finds that its substantial effect on the labor supply of the elderly is concentrated on informal employment.
Keywords: African Research